Automatic Door Control System With Body Temperature Sensor - Dwi Iskandar; Erik Wisnu Nugroho; Dewi Rahmawati; Ikhwan Rozikin (Institut Teknologi Bisnis AAS Indonesia, 2021)
Conventional doors usually consist of a key housing and a key saddle to open it. In the current pandemic situation that has arisen due to COVID-19, so every human being is required to take precautions such as wearing a mask, keeping a distance, washing hands, not touching anything if not unnecessary. Research Methods Literature Study, Collection of supporting materials and tools, Program Design and Realization, Testing and Analysis of Program results, Making Final Report. The automatic door control system with a body temperature sensor is a prototype made to prevent the spread of COVID-19 by reducing direct physical contact that is spread through droplets attached to conventional doorknobs. Technology can be implemented in crowded areas such as shopping centers, offices, restaurants that are placed in indoor areas or indoor areas that are not exposed to direct sunlight. The components used are Arduino Uno Rev 3, Infrared Sensor, MLX90614 Temperature Sensor, 16x2 LCD, Buzzer, L298N Motor Driver, DC Motor, 12v Adapter, and LED